WRITING STRATEGIES EMPLOYED BY SECOND LANGUAGE LEARNERS - Arina Shofiya (Pusat Pengembangan Bahasa IAIN Tulungagung, 2013)
In second language context, learning writing is often considered burdensome for learners due to the complexity of the process in producing a piece of writing. To succeed in L2 writing, some strategies are employed by learners which are different from learners to learners across L2 contexts or nations. This article attempts to review some theories in L2 writing and altogether, synthesizes some findings of research about strategies employed by L2 learners in writing. Theoretically, there are at least four theory of L2 writing, namely, Contrastive Rhetoric Theory, Cognitive Development Theory, Communication Theory, and Social Constructionist Theory. Meanwhile, there is storage of strategies in L2 writing different in name but similar in practice.